Effect of chitosan-carvacrol edible coatings on the quality and shelf life of tilapia (Oreochromis niloticus) fillets stored in ice - CHAPARRO-HERNÁNDEZ,Saraí (2015)
Abstract Fish consumption has increased in recent years. However, fish meat is highly perishable, which demonstrates the need for technologies to preserve its quality. Edible coatings (EC) might provide an alternative to extend the shelf life of fish. The goal of this study was to evaluate the effect of EC of chitosan (C) in combination with carvacrol (CAR) on the physical and microbiological changes of tilapia fillets. Fillets were submerged for two minutes in different treatments (T1: control; T2: C 2%; T3: C 2% + 0.125% CAR; T 4: C 2% + 0.25% CAR). At the end of storage, T1 and T2 showed the lowest values of total volatile bases (TVB). The color parameters L*, a* and b* varied from each treatment. The texture decreased and the different treatments reduced the microbial population in relation to the control; T3 and T4 were the most effective. These results show that the use of C with CAR might be an alternative method to preserve the quality and safety of tilapia fillets.